2010
DOI: 10.1590/s0103-21002010000300004
|View full text |Cite
|
Sign up to set email alerts
|

As (im)possibilidades de brincar para o escolar com câncer em tratamento ambulatorial

Abstract: Objectives: To identify the mediators of play in the lives of children with cancer in outpatient treatment, and review the opportunities of using them, considering the limitations imposed by the disease and the treatment. Methods: Qualitative research, according to the creative and sensitive method implemented; it was focused on group dynamics "Playing on stage." Twelve (12) children participated, who were being treated for cancer in an outpatient service at a hospital in Rio de Janeiro. Results: Two themes em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
0
4
0
11
Order By: Relevance
“…Estudiosos ressaltam que o brincar é uma necessidade, tanto da criança saudável quanto em processo de adoecimento. 8 Por meio dele a criança cria, recria, socializa-se, aprende e se desenvolve, fazendo com que essa necessidade não deixe de existir quando a criança adoece.…”
Section: Introductionunclassified
“…Estudiosos ressaltam que o brincar é uma necessidade, tanto da criança saudável quanto em processo de adoecimento. 8 Por meio dele a criança cria, recria, socializa-se, aprende e se desenvolve, fazendo com que essa necessidade não deixe de existir quando a criança adoece.…”
Section: Introductionunclassified
“…The following steps were taken according to the analytical method: floating reading through an exhaustive contact with the material; exploitation of the material, in which after the reading of the raw information, the testimonies were grouped to the pre-established thematic units that provided answers to the aims and the hypothesis raised in this research; and finally, the treatment and interpretation of the results found. (6) According to Resolution 466/2012 of the Brazilian National Health Council, which defines the directives and regulatory standards of researches involving human beings, this research project was previously submitted and approved by the Committee of Ethics in Research of the hospital in which it was performed (Protocol #276/11).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the nurses have a fundamental role in the caring for these subjects, as they work in direct assistance to both, generating an improvement in quality of life. (6,7) It is known that cancer also generates adverse effects due to the chemotherapeutic elements of the treatment, but it also affects the psychosocial side, provoking sadness, anger, depression, and other states. Therefore, to minimize these effects, it is necessary that there is support from a multiprofessional team that helps the child and his family, transforming the treatment to a less impactful approach, improving the quality of life of the subjects involved.…”
Section: Introductionmentioning
confidence: 99%
“…4 Additionally, families' daily lives change when dealing with a child's illness and that situation is worsened by mothers' distress and unpreparedness. 5 The hospitalization process requires an interaction among people in the same physical and temporal space, enabling the construction of cultural standards derived from the fact that human beings are incomplete, and become complete throughout time through the interactions they establish. 6 The recommendation for hospitalization, usually in oncology pediatric intensive care units (PICU), are a consequence of cancer treatment itself since it usually requires surgeries, chemotherapy, and radiotherapy, which may lead to clinical problems produced by the treatment's side effects.…”
Section: Introductionmentioning
confidence: 99%